Hydrologic and water quality impacts and biomass production potential on marginal land. (October 2015) - Feng, Qingyu; Chaubey, Indrajeet; Her, Young Gu; Cibin, Raj; Engel, Bernard; Volenec, Jeffrey; Wang, Xiuying
Abstract: Marginal land is proposed as viable land resources for biofuel production. However, environmental impacts of perennial biomass production on marginal lands is not clear. This study defined three marginal land types and assessed their availability and potential for biofuel production in the St. Joseph River watershed. The potential impacts were evaluated using the Agricultural Policy/Environmental eXtender (APEX) model. The total area of marginal land was estimated to be 611 km 2 covering 21.7% of the watershed. 161 and 207 million liters of bioethanol could be produced from the marginal land utilizing switchgrass and Miscanthus, respectively. Converting marginal land currently under corn/soybean production to switchgrass and Miscanthus reduced water yield by 13.4–36.3% and improved water quality by reducing soil erosion by 27%–98%. Similarly, total nitrogen losses were reduced by 30–91% and total phosphorus losses were reduced by 65–76%, respectively, at the field scales under various energy crop production scenarios. Highlights: 21.7% of the St. Joseph River watershed are identified as marginal land. 161 to 207 million liter bioethanol could be produced from marginal land. Water yield will potentially be reduced by 13%–36% at field scale. Soil erosion will potentially be reduced by 27%–90% at field scale. Nitrogen and phosphorus losses will generally be reduced at field scale.